miR-223-3p carried by cancer-associated fibroblast microvesicles targets SORBS1 to modulate the progression of gastric cancer - Xiaoli Jin; Xi Qiu; Yi Huang; Hang Zhang; Kaibo Chen (Cancer Cell International, 2022)
Abstract Background Cancer-associated fibroblasts (CAFs) aggravate gastric cancer (GC) development. Methods Combined with bioinformatics analysis and literature review, miR-223-3p had high expression in microvesicles (MVs) derived from GC CAFs, and it could modulate SORBS1. miR-223-3p and SORBS1 mRNA levels were assessed by qRT-PCR. The levels of CAFs markers, MVs markers, epithelial-mesenchymal transition (EMT)-associated proteins, and SORBS1 protein were assessed by western blot. MVs isolated from fibroblasts were observed by transmission electron microscopy. Combined with immunofluorescence and co-culture experiments, GC cells were determined to absorb MVs carrying miR-223-3p. Cell functions were measured using CCK-8, transwell, flow cytometry and colony formation assays. The binding of miR-223-3p and SORBS1 was determined by dual-luciferase assay and RNA immunoprecipitation. The cancer-promoting effect of MVs carrying miR-223-3p on experimental animals was verified in vivo by tumor-bearing experiment in nude mice. Results miR-223-3p was upregulated in the MVs secreted by GC CAFs and could be transmitted to GC cells through MVs, to boost the malignant progression of tumor cells. Additionally, it was also revealed that miR-223-3p targeted SORBS1 and accelerated progression along with EMT in GC. Conclusions CAFs-derived MVs could carry miR-223-3p to GC cells to target SORBS1, thereby promoting the malignant progression of GC.